Dimensi Kemanusiaan Dalam Sistem Ekonomi Islam: Sebuah Kajian Dengan Pendekatan Filsafat Hukum Islam - Tamam, Ahmad Badrut (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2018)
Economics in the perspective of Islam is not only aimed at finding material but also non-material. Economics in Islam must be professionally managed and compatible with Islamic values ​​because economics in Islam has two dimensions: vertical and horizontal. Therefore, the Koran has offered the concept of economics without loss (tijarah lan tabur) for all entrepreneurs, namely despite losing financially, but generating profits in the form of religious awards. Thus, this kind of economy can only be obtained by carefully observing the vertical and horizontal dimensions of the economy in Islam. Based on this view, the author emphasizes that the Islamic economic system needs to be fulfilled by human dimensions in all economic fields such as production, consumption, distribution, and circulation. This article tries to identify the application of humanitarian principles to the Islamic economic system.